PENGARUH ORGANIZATIONAL SILENCE (OS) DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN SAMPOERNA - LATIFATUR ROKHMAH, NUR (Jurnal Ilmu Manajemen (JIM), 2017)
Sampoerna Employee Cooperative hereinafter abbreviated KOPKAR Sampoerna is one of the economic actors in the private sector is one of the Cooperative Enterprises that serve savings and loan sales of basic materials to employees Sampoerna. This Kopkar sampoerna service is not only manifested in the performance of the task in accordance with the standard of work procedures but also beyond that or the behavior of organizational citizenship behavior (OCB) shown by employees.This study aims to determine and explain the effect of organizational silence (OS) and job satisfaction on organizational citizenship behavior (OCB) on Kopkar sampoerna employees. This research is a type of causal research using quantitative approach with population of 152 people and sampling technique using simple random sampling with sample of 60 employees. Data analysis techniques using smartPLS software help.The results of this study showed that organizational silence (OS) had negative and significant effect on organizational citizenship behavior (OCB) and showed that job satisfaction had positive and significant effect on organizational citizenship behavior (OCB). Keywords: Organizational Citizenship Behavior (OCB), Organizational Silence (OS), Job Satisfaction